KONTRIBUSI KEKUATAN MAKSIMUM EKSTREMITAS ATAS DAN BAWAH TERHADAP START DAN PERFORMA RENANG BEBAS 50M - Ceri, Nicole Chiara; Irawan, Roy Januardi (Pedagogi: Jurnal Ilmiah Pendidikan, 2025)
This study is a correlational research using a quantitative approach. It specifically aims to examine the contribution of upper and lower limb maximal strength during the start phase and overall performance in 50-meter freestyle sprint swimming among athletes from the Club Science Swimming Team. The study involves two independent variables (upper limb maximal strength and lower limb maximal strength) and one dependent variable (sprint swimming performance). Data were collected using a timing device to measure the speed of each athlete in the 50-meter freestyle sprint. The sample consisted of 10 athletes selected through purposive sampling, based on criteria set by the study—namely, swimmers aged between 8 and 12 years old. The data analysis involved normality testing, Pearson correlation, and multiple regression analysis. The results show that both upper and lower limb maximal strength have an influence on sprint performance. However, regression analysis revealed that the contribution of both variables was not statistically significant. Among the two, lower limb strength contributed more to swimming speed compared to upper limb strength.